Analisis Volume Sedimen Waduk Wonogiri Di Muara Sungai Keduang - Asmoro, Anton Tri; , Purwanti Sri Pudyastuti, ST., M.Sc, Ph.D; , Ir. Isnugroho, CES (2015)
Soeharto, the second president of Indonesia, inaugurated Wonogiri multipurpose Dam on November 17th, 1981. This is the only ‐ biggest Dam located in the main river of Bengawan Solo. The function of it is to control flood on the area of 400 million m3, to be source of hydroelectric power plant for, and to be water supply for PDAM, as well as for argiculture, tourism, and fishery. Wonogiri reservoir water source comes from six rivers, including the River Keduang which causes the biggest sedimentation, due to very close to the intake. Sediment from the river Keduang very disturbing. To overcome this new spillway was built closer to the river Keduang. This study was conducted to determine the amount of sediment washed into the river The reservoir by Keduang. This study was conducted to determine the amount of sediment washed into river Keduang by the reservoir. Analysis of sediment calculation is in estuary Keduang. The total volume of sediment from the river Keduang using Meyer Peter and Muller (MPM). The data used in the analyst is: Data TMA in AWLR, Grain size, Cross secton. The result of the calculation analysis The reservoir sediments in estuary Keduang from 2006 to 2012 is = 6,184,309.84 m³ / year. Calculations related to the discharge of sediment in the estuary Keduang, the analysis obtained Rating Curve equation: Y = 0,014685801.X0,351965501